Exploring the Impact of Earnings Management and Tax Planning on Book-Tax Differences in Mining Companies - Denny Putri Hapsari; Denny Kurnia (International Journal of Management Research and Economics, 2025)
This study aims to examine the effect of earnings management and tax planning on book-tax differences in public mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The data was obtained from the financial statements and annual reports published by the IDX. A quantitative approach was employed to assess the impact of earnings management and tax planning on book-tax differences. Secondary data, in the form of financial statements for the 2017-2021 reporting period, was gathered using purposive sampling from the Indonesia Stock Exchange website (www.idx.co.id). Out of 47 listed mining companies, 15 met the criteria and were selected as the sample. Data analysis was conducted using SPSS. The results revealed that earnings management has a significant positive effect on book-tax differences, while tax planning does not have a significant impact. These findings have important implications for company management in effectively managing book-tax differences and minimizing potential risks associated with discrepancies between financial statements and tax reports. Additionally, the study underscores the importance of considering the specific tax regulations and context of each country or region, as differing tax rules can influence how earnings management and tax planning affect book-tax differences.